Enhancing Students’ Self-Efficacy in Creativity and Learning Performance in the Context of English Learning: The Use of Self-Assessment Mind Maps - Yan, Zi; Lee, John Chi-Kin; Hui, Sammy King Fai; Lao, Hongling (Frontiers in Psychology, 2022)
Creativity is an important 21st Century skill that enhances students’ ability to see new opportunities, confront new challenges, and adapt flexibly to the changing study, work and life situations. To nurture students with strong self-efficacy in creative thinking is as important as the contexts and strategies involved in its application. But how to develop sustainable intervention (without generating excessive workload for teachers) to promote students’ self-efficacy in creativity is a long-lasting challenge. This study presents a simple and relatively cost-effective instructional intervention, i.e., self-assessment mind maps, and examines its effect on students’ self-efficacy in creativity, self-efficacy in learning English, and academic performance in English learning. A pretest-posttest nonequivalent design was adopted for the treatment and control groups of students in a Hong Kong local primary school in 2021/22 Spring semester. The results show that students from the experimental group significantly outperformed those from the control group on self-efficacy in creativity after the intervention. However, the intervention did not improve students’ self-efficacy and academic performance in English language learning. The findings demonstrate the potential of self-assessment mind maps as an effective and sustainable instruction intervention to promote students’ higher-order abilities. This study sheds light on designing sustainable instructional strategies for empowerment in creativity.